Lithium iron phosphate positive electrode material and preparation method and application thereof

Through specific preparation methods, the ZIF-8 auxiliary regulatory and rare earth element oxides are covered with the problem of low diffusion rate and structural stability of lithium iron phosphate battery positive materials, and the battery multiplication and cycle performance significantly improves the battery.

CN119370822APending Publication Date: 2025-01-28GEM WUXI ENERGY MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411559411.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing lithium iron phosphate battery positive electrode materials have problems such as low diffusion rate, low conductivity and poor material structural stability, resulting in limited charging and discharging rates of the battery and poor rate performance and cycle performance.

Method used

By mixing the iron source, phosphorus source, lithium source, and ZIF-8 front-drive body, it is grinded, dry, first sintering and second sintering, combined with rare earth element oxides to prepare the lithium iron phosphate positive pole material with porous structure Essence

Benefits of technology

This method significantly improves the structural stability and electrochemical properties of the positive pole material, enhances the diffusion rate of lithium ions, improves the multiplier performance and circulation performance, and especially performs excellent under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117479380000111
    Figure BDA0005117479380000111
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a lithium iron phosphate positive electrode material and a preparation method and application thereof. The preparation method of the lithium iron phosphate positive electrode material provided by the invention comprises the following steps: 1) mixing an iron source, a phosphorus source, a lithium source and a ZIF-8 precursor, grinding and drying to obtain composite powder; 2) performing first sintering on the composite powder obtained in the step 1) to obtain a first sintered material; and 3) mixing a rare earth element oxide with the first sintering material obtained in the step 2), and carrying out second sintering to obtain the lithium iron phosphate positive electrode material. The lithium iron phosphate positive electrode material prepared by the specific preparation method is high in rate capability and cycle performance, and particularly high in cycle performance under a high-temperature condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a lithium iron phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, lithium iron phosphate (LFP) cathode materials have attracted extensive attention from researchers. Compared with traditional lithium cobalt oxide cathode materials, LFP materials are not only safer, but also cheaper and more environmentally friendly in production, and can meet the needs of various application scenarios. Therefore, this material is widely used in electric vehicles, energy storage systems, mobile power supplies and other fields.

[0003] However, the low diffusion rate and conductivity of lithium ions in LFP and the poor structural stability of LFP materials have become obstacles to the commercialization of LFP. This means that the transmission speed of lithium ions in LFP batteries is relatively slow, which limits the battery's charge and discharge rate, and results in poor rate performance and cycle performance during actual charge and discharge, affecting its performance in industrial applications. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of low diffusion rate, low conductivity and poor material structure stability of the existing lithium iron phosphate battery positive electrode material, thereby providing a lithium iron phosphate positive electrode material and its preparation method and application.

[0005] The present invention provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0006] 1) mixing an iron source, a phosphorus source, a lithium source and a ZIF-8 precursor, grinding and drying to obtain a composite powder;

[0007] 2) subjecting the composite powder obtained in step 1) to a first sintering to obtain a sintered material;

[0008] 3) Mixing the rare earth element oxide with the first sintered material obtained in step 2), and performing a second sintering to obtain the lithium iron phosphate positive electrode material.

[0009] Preferably, the iron source in step 1) is selected from at least one of FePO4, Fe2(SO4)3, and Fe(NO4)3;

[0010] The phosphorus source is selected from at least one of FePO4 and H3PO4;

[0011] The lithium source is selected from at least one of Li2CO3, LiOH, and LiOH·H2O;

[0012] The ratio of the molar amount of the iron element in the iron source, the molar amount of the phosphorus element in the phosphorus source and the molar amount of the lithium element in the lithium source is 1:(0.5-1.5):(1-3).

[0013] Optionally, the iron source and the phosphorus source can be selected from the same substance. For example, FePO4 can be selected as the iron source and the phosphorus source at the same time.

[0014] Preferably, the mass ratio of the iron source to the ZIF-8 precursor in step 1) is (1-3): (0.3-1);

[0015] Optionally, in step 1), the iron source, phosphorus source, lithium source, ZIF-8 precursor and water are mixed, and then ground and dried to obtain a composite powder;

[0016] Optionally, after the iron source, phosphorus source, lithium source, ZIF-8 precursor and water are mixed, the mass percentage of water in the mixture is 80-90%;

[0017] Optionally, the grinding speed is 500-2000 rpm, and the grinding time is 2-6 h.

[0018] Preferably, the drying in step 1) specifically comprises: adjusting the ground material to a solid content of 15%-30%, and then spray drying;

[0019] Optionally, the material inlet temperature of the spray drying is 200-240°C, the material outlet temperature is 100-120°C, and the feed rate is 60-100kg / h.

[0020] Preferably, in step 2), the first sintering comprises first sintering at 300-600° C. for 4-6 hours, and then sintering at 700-800° C. for 10-15 hours;

[0021] The first sintering atmosphere includes an oxygen atmosphere.

[0022] Preferably, the rare earth element oxide in step 3) is at least one selected from lanthanum oxide, cerium oxide, praseodymium oxide, and samarium oxide;

[0023] Optionally, the rare earth element oxide is selected from at least one of La2O3, CeO2, PrO2, Pr2O3, and Sm2O3.

[0024] Preferably, the mass ratio of the rare earth element oxide in step 3) to the sintered material obtained in step 2) is (0.05-0.2):1.

[0025] Preferably, in step 3), the second sintering temperature is 400-700° C., and the second sintering time is 4-10 h;

[0026] The second sintering atmosphere includes an oxygen atmosphere.

[0027] Optionally, the second sintering further includes the steps of grinding and screening.

[0028] The present invention provides a lithium iron phosphate positive electrode material, which is prepared by the above-mentioned method for preparing the lithium iron phosphate positive electrode material.

[0029] The present invention provides an application of the above-mentioned lithium iron phosphate positive electrode material in a lithium ion battery.

[0030] The technical solution of the present invention has the following advantages:

[0031] The preparation method of the lithium iron phosphate positive electrode material provided by the present invention comprises the following steps: 1) mixing an iron source, a phosphorus source, a lithium source and a ZIF-8 precursor, and obtaining a composite powder after grinding and drying; 2) subjecting the composite powder obtained in step 1) to a first sintering to obtain a sintered material; 3) mixing a rare earth element oxide with the sintered material obtained in step 2) and subjecting the mixture to a second sintering to obtain the lithium iron phosphate positive electrode material. The rare earth element coating of the present invention can form a protective film on the surface of the positive electrode material, effectively preventing the direct contact between the material and the electrolyte, reducing the occurrence of side reactions, and helping to inhibit the phase change of the material during the charge and discharge process, thereby enhancing the structural stability of the material, reducing the capacity decay caused by structural changes, and significantly improving the capacity retention rate of the positive electrode material in the battery, so that the battery can withstand more charge and discharge cycles while maintaining a higher capacity, improving the cycle stability, and extending the service life of the battery; at the same time, the present invention uses ZIF-8 to assist in regulating the morphology of the NCA ternary positive electrode material, so that a large number of porous sites appear, and prepare a ternary positive electrode material with a porous structure. The porous structure has high permeability, electrical conductivity, mechanical strength and chemical stability, and the pore structure can be designed and manipulated. The high specific surface area of ​​the obtained positive electrode material will also increase its rate performance, increase the diffusion rate of lithium ions, and improve the conductivity of the positive electrode material, thereby improving the cycle performance. ZIF-8 assists in regulating the porous morphology of the NCA ternary cathode material, forming a porous morphology inside the cathode material, and the porous structure on its surface is matched with a protective film coated with rare earth elements, which further reduces the direct contact area ratio between the cathode material and the electrolyte, significantly improving the cycle performance, especially the cycle performance. The lithium iron phosphate cathode material prepared by the specific preparation method of the present invention has high rate performance and cycle performance, especially high cycle performance under high temperature conditions. DETAILED DESCRIPTION

[0032] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0033] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0034] The ZIF-8 precursor of the present invention is composed of zinc ions (Zn 2+ ) and 2-methylimidazole (2-MiM) coordinated to form a type of metal-organic framework, with a CAS number of 59061-53-9.

[0035] Example 1

[0036] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0037] 1) 1.524 g FePO4, 0.74 g Li2CO3, 18 ml deionized water, and 0.508 g ZIF-8 precursor were ground at 700 rpm for 3 h. After grinding, the ground material was adjusted to a solid content of 23%, and then spray-dried. The material inlet temperature of the spray-dried material was 220° C., the material outlet temperature was 110° C., and the feed rate was 80 kg / h. After spray drying, a composite powder was obtained;

[0038] 2) placing the composite powder obtained in step 1) into a box-type atmosphere furnace under a pure oxygen atmosphere, sintering at 500° C. for 4 h and then sintering at 724° C. for 10 h to obtain a sintered material;

[0039] 3) The rare earth element oxide CeO2 is mixed with the sintered material obtained in step 2) at a mass ratio of 0.13:1, and sintered at 500°C for 6 hours in a pure oxygen atmosphere. After sintering, the lithium iron phosphate positive electrode material is obtained by roller ultrafine grinding and sieving.

[0040] Example 2

[0041] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0042] 1) 1.524 g FePO4, 0.74 g Li2CO3, 18 ml deionized water, and 0.381 g ZIF-8 precursor were ground at 700 rpm for 3 h. After grinding, the ground material was adjusted to a solid content of 23%, and then spray-dried. The material inlet temperature of the spray-dried material was 220° C., the material outlet temperature was 110° C., and the feed rate was 80 kg / h. After spray drying, a composite powder was obtained;

[0043] 2) placing the composite powder obtained in step 1) into a box-type atmosphere furnace under a pure oxygen atmosphere, sintering at 500° C. for 4 h and then sintering at 700° C. for 10 h to obtain a sintered material;

[0044] 3) The rare earth element oxide CeO2 is mixed with the sintered material obtained in step 2) at a mass ratio of 0.13:1, and sintered at 500°C for 4 hours in a pure oxygen atmosphere. After sintering, the lithium iron phosphate positive electrode material is obtained by roller ultrafine grinding and sieving.

[0045] Example 3

[0046] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0047] 1) 1.524 g FePO4, 0.74 g Li2CO3, 18 ml deionized water, and 0.762 g ZIF-8 precursor were ground at 700 rpm for 3 h. After grinding, the ground material was adjusted to a solid content of 23%, and then spray-dried. The material inlet temperature of the spray-dried material was 220° C., the material outlet temperature was 110° C., and the feed rate was 80 kg / h. After spray drying, a composite powder was obtained;

[0048] 2) placing the composite powder obtained in step 1) into a box-type atmosphere furnace under a pure oxygen atmosphere, sintering at 300° C. for 3.5 hours and then sintering at 800° C. for 15 hours to obtain a sintered material;

[0049] 3) The rare earth element oxide CeO2 is mixed with the sintered material obtained in step 2) at a mass ratio of 0.13:1, and sintered at 700°C for 6 hours in a pure oxygen atmosphere. After sintering, the lithium iron phosphate positive electrode material is obtained by roller ultrafine grinding and sieving.

[0050] Example 4

[0051] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0052] 1) 1.524 g FePO4, 0.74 g Li2CO3, 18 ml deionized water, and 0.508 g ZIF-8 precursor were ground at 500 rpm for 6 h. After grinding, the ground material was adjusted to a solid content of 15%, and then spray-dried. The material inlet temperature of the spray-dried material was 240° C., the material outlet temperature was 100° C., and the feed rate was 100 kg / h. After spray drying, a composite powder was obtained;

[0053] 2) placing the composite powder obtained in step 1) into a box-type atmosphere furnace under a pure oxygen atmosphere, sintering at 300° C. for 6 h and then sintering at 700° C. for 15 h to obtain a sintered material;

[0054] 3) The rare earth element oxide La2O3 is mixed with the sintered material obtained in step 2) at a mass ratio of 0.05:1, and sintered at 700°C for 4 hours in a pure oxygen atmosphere. After sintering, the mixture is ultrafinely ground by roller pressing and sieved to obtain the lithium iron phosphate positive electrode material.

[0055] Example 5

[0056] This embodiment provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0057] 1) 1.524 g FePO4, 0.74 g Li2CO3, 19 ml deionized water, and 0.508 g ZIF-8 precursor were ground at 700 rpm for 3 h. After grinding, the ground material was adjusted to a solid content of 23%, and then spray-dried. The material inlet temperature of the spray-dried material was 220° C., the material outlet temperature was 110° C., and the feed rate was 80 kg / h. After spray drying, a composite powder was obtained;

[0058] 2) placing the composite powder obtained in step 1) into a box-type atmosphere furnace under a pure oxygen atmosphere, sintering at 600° C. for 4 h and then sintering at 800° C. for 15 h to obtain a sintered material;

[0059] 3) The rare earth element oxide PrO2 is mixed with the sintered material obtained in step 2) at a mass ratio of 0.2:1, and sintered at 400°C for 40 hours in a pure oxygen atmosphere. After sintering, the lithium iron phosphate positive electrode material is obtained by roller ultrafine grinding and sieving.

[0060] Comparative Example 1

[0061] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0062] 1) 1.524 g FePO4, 0.74 g Li2CO3, and 18 ml deionized water were ground at 700 rpm for 3 h. After grinding, the ground material was adjusted to a solid content of 23%, and then spray-dried. The material inlet temperature of the spray-dried material was 220° C., the material outlet temperature was 110° C., and the feed rate was 80 kg / h. After spray drying, a composite powder was obtained;

[0063] 2) placing the composite powder obtained in step 1) into a box-type atmosphere furnace under a pure oxygen atmosphere, sintering at 500° C. for 4 h and then sintering at 724° C. for 10 h to obtain a sintered material;

[0064] 3) The rare earth element oxide CeO2 is mixed with the sintered material obtained in step 2) at a mass ratio of 0.13:1, and sintered at 500°C for 6 hours in a pure oxygen atmosphere. After sintering, the lithium iron phosphate positive electrode material is obtained by roller ultrafine grinding and sieving.

[0065] Comparative Example 2

[0066] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0067] 1) 1.524 g FePO4, 0.74 g Li2CO3, 18 ml deionized water, and 0.508 g ZIF-8 precursor were ground at 700 rpm for 3 h. After grinding, the ground material was adjusted to a solid content of 23%, and then spray-dried. The material inlet temperature of the spray-dried material was 220° C., the material outlet temperature was 110° C., and the feed rate was 80 kg / h. After spray drying, a composite powder was obtained;

[0068] 2) placing the composite powder obtained in step 1) into a box-type atmosphere furnace under a pure oxygen atmosphere, sintering at 500° C. for 4 h and then sintering at 724° C. for 10 h to obtain a sintered material;

[0069] 3) The sintered material obtained in step 2) is sintered at 500° C. for 6 h in a pure oxygen atmosphere. After sintering, it is subjected to roller ultrafine grinding and sieving to obtain the lithium iron phosphate positive electrode material.

[0070] Comparative Example 3

[0071] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0072] 1) 1.524 g FePO4, 0.74 g Li2CO3, and 18 ml deionized water were ground at 700 rpm for 3 h. After grinding, the ground material was adjusted to a solid content of 23%, and then spray-dried. The material inlet temperature of the spray-dried material was 220° C., the material outlet temperature was 110° C., and the feed rate was 80 kg / h. After spray drying, a composite powder was obtained;

[0073] 2) placing the composite powder obtained in step 1) into a box-type atmosphere furnace under a pure oxygen atmosphere, sintering at 500° C. for 4 h and then sintering at 724° C. for 10 h to obtain a sintered material;

[0074] 3) The sintered material obtained in step 2) is sintered at 500° C. for 6 h in a pure oxygen atmosphere. After sintering, it is subjected to roller ultrafine grinding and sieving to obtain the lithium iron phosphate positive electrode material.

[0075] Comparative Example 4

[0076] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0077] 1) 1.524 g FePO4, 0.74 g Li2CO3, 18 ml deionized water, and 0.508 g ZIF-8 precursor were ground at 700 rpm for 3 h. After grinding, the ground material was adjusted to a solid content of 23%, and then spray-dried. The material inlet temperature of the spray-dried material was 220° C., the material outlet temperature was 110° C., and the feed rate was 80 kg / h. After spray drying, a composite powder was obtained;

[0078] 2) placing the composite powder obtained in step 1) into a box-type atmosphere furnace under a pure oxygen atmosphere, sintering at 500° C. for 4 h and then sintering at 724° C. for 10 h to obtain a sintered material;

[0079] 3) Al2O3 and the sintered material obtained in step 2) are mixed at a mass ratio of 0.13:1, sintered at 500°C for 6 hours in a pure oxygen atmosphere, and after sintering, the lithium iron phosphate positive electrode material is obtained by roller ultrafine grinding and sieving.

[0080] Comparative Example 5

[0081] This comparative example provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:

[0082] 1) sintering the ZIF-8 precursor at 900° C. for 2 h to obtain a pretreated ZIF-8 precursor;

[0083] 2) 1.524 g FePO4, 0.74 g Li2CO3, 18 ml deionized water, and 0.508 g of the pretreated ZIF-8 precursor obtained in step 1) were ground at 700 rpm for 3 h. After grinding, the ground material was adjusted to a solid content of 23%, and then spray-dried. The material inlet temperature of the spray-dried material was 220° C., the material outlet temperature was 110° C., and the feed rate was 80 kg / h. After spray drying, a composite powder was obtained;

[0084] 3) placing the composite powder obtained in step 2) into a box-type atmosphere furnace under a pure oxygen atmosphere, sintering at 500° C. for 4 h and then sintering at 724° C. for 10 h to obtain a sintered material;

[0085] 4) The rare earth element oxide CeO2 is mixed with the sintered material obtained in step 3) at a mass ratio of 0.13:1, and sintered at 500°C for 6 hours in a pure oxygen atmosphere. After sintering, the lithium iron phosphate positive electrode material is obtained by roller ultrafine grinding and sieving.

[0086] Test Case

[0087] The lithium iron phosphate positive electrode material obtained in Example 1-5 and Comparative Example 1-5 was used as the positive electrode main material to prepare the positive electrode sheet. N-methylpyrrolidone was used as the dispersant. The positive electrode main material: carbon black: PVDF (polyvinylidene fluoride): dispersant were mixed at a mass ratio of 90:5:5:100 to prepare a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil (coating surface density 12.50 mg / cm 2 ), drying in an oven to remove the dispersant, and obtaining a positive electrode sheet; using a lithium metal sheet as a negative electrode sheet, an electrolyte being a mixed solute of lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC) and dimethyl carbonate, with a volume ratio of ethylene carbonate (EC) to dimethyl carbonate (DMC) of 1:1, a concentration of lithium hexafluorophosphate in the electrolyte of 1 mol / L, and a diaphragm being a Celgard 2500 diaphragm, in an argon atmosphere of a glove box, assembling a CR2032 type button lithium ion half-cell in the order of a negative electrode sheet, an electrolyte, a diaphragm, an electrolyte, and a positive electrode sheet.

[0088] The button cell was placed in the Blue Electric test system for electrical performance testing. Test conditions: Test temperature 25°C, first cycle charged to 4.25V at a rate of 0.2C, then discharged to 2.5V at a rate of 0.2C, this is one cycle, then charged and discharged at a rate of 0.2C for 49 cycles, a total of 50 cycles, and the capacity retention rate after 50 cycles of 0.2C was tested; the test results are shown in Table 1.

[0089] The above button battery was taken and placed in the Blue Electric test system for electrical performance testing. The test conditions were as follows: the test temperature was 25°C, the first cycle was charged to 4.25V at a rate of 0.5C, and then discharged to 2.5V at a rate of 0.2C, which was one cycle process, and then the charge and discharge cycle was repeated for 49 cycles at a rate of 0.5C, for a total of 50 cycles, and the capacity retention rate after 50 cycles at 0.5C was tested; the test results are shown in Table 1.

[0090] The above button cell was taken and put into the blue electric test system for electrical performance test. The test conditions were as follows: the test temperature was 60°C, the first cycle was charged to 4.25V at a rate of 0.2C, and then discharged to 2.5V at a rate of 0.2C, which was one cycle process, and then the charge and discharge cycle was repeated for 49 cycles at a rate of 0.2C, for a total of 50 cycles, and the capacity retention rate after 50 cycles of 0.2C was tested; the test results are shown in Table 1.

[0091] Table 1

[0092]

[0093] As can be seen from Table 1, the cycle performance and rate performance of the lithium iron phosphate cathode material obtained by the specific preparation method of the present invention are significantly better than those of the lithium iron phosphate cathode material obtained in the comparative example, especially the improvement of the 60°C high temperature cycle capacity retention rate is obvious. In comparative example 5, the ZIF-8 material after calcination pretreatment is used, which makes it difficult to make the subsequent sintered material have a porous structure, and even if a small number of pores are formed, they are uneven, and its rate performance and cycle performance are worse than those of the embodiments of the present invention, indicating that the specific doping and sintering sequence of the present application plays a vital role in forming a specific morphology of the cathode material and improving its electrochemical performance.

[0094] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: 1) mixing an iron source, a phosphorus source, a lithium source and a ZIF-8 precursor, grinding and drying to obtain a composite powder; 2) subjecting the composite powder obtained in step 1) to a first sintering to obtain a sintered material; 3) Mixing the rare earth element oxide with the first sintered material obtained in step 2), and performing a second sintering to obtain the lithium iron phosphate positive electrode material.

2. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The iron source in step 1) is selected from at least one of FePO4, Fe2(SO4)3, and Fe(NO4)3; The phosphorus source is selected from at least one of FePO4 and H3PO4; The lithium source is selected from at least one of Li2CO3, LiOH, and LiOH·H2O; The ratio of the molar amount of the iron element in the iron source, the molar amount of the phosphorus element in the phosphorus source and the molar amount of the lithium element in the lithium source is 1:(0.5-1.5):(1-3).

3. The method for preparing the lithium iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The mass ratio of the iron source to the ZIF-8 precursor in step 1) is (1-3): (0.3-1).

4. The method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 3, characterized in that: The drying in step 1) specifically includes: adjusting the ground material to a solid content of 15%-30%, and then spray drying; Optionally, the material inlet temperature of the spray drying is 200-240°C, the material outlet temperature is 100-120°C, and the feed rate is 60-100kg / h.

5. The method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 4, characterized in that: In step 2), the first sintering includes sintering at 300-600° C. for 4-6 hours, and then sintering at 700-800° C. for 10-15 hours; The first sintering atmosphere includes an oxygen atmosphere.

6. The method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: The rare earth element oxide in step 3) is at least one selected from lanthanum oxide, cerium oxide, praseodymium oxide, and samarium oxide; Optionally, the rare earth element oxide is selected from at least one of La2O3, CeO2, PrO2, Pr2O3, and Sm2O3.

7. The method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 6, characterized in that: The mass ratio of the rare earth element oxide in step 3) to the sintered material obtained in step 2) is (0.05-0.2):

1.

8. The method for preparing the lithium iron phosphate positive electrode material according to any one of claims 1 to 7, characterized in that: In step 3), the second sintering temperature is 400-700° C., and the second sintering time is 4-10 hours; The second sintering atmosphere includes an oxygen atmosphere.

9. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the preparation method of the lithium iron phosphate positive electrode material according to any one of claims 1 to 8.

10. Use of the lithium iron phosphate positive electrode material according to claim 9 in lithium ion batteries.

Citation Information

Cited By

  • High-temperature-resistant low-iron-dissolution lithium iron phosphate material as well as preparation method and application thereof

    CN120664513A